Factors influencing noncompliance with bicycle passing distance laws. (June 2018) - Debnath, Ashim Kumar; Haworth, Narelle; Schramm, Amy; Heesch, Kristiann C.; Somoray, Klaire
Highlights: Bicycle passing distance measured using a naturalistic study design. Lower compliance rates observed at road curves and narrow traffic lanes. Greater compliance rates observed at 60 km/h roads. Motorcycles were more compliant than passenger cars. Rider age, gender, clothing, or bike type did not influence compliance status. Abstract: Many jurisdictions around the world have implemented laws to require a minimum distance when motor vehicles pass cyclists, but research into the factors influencing passing distances has produced inconsistent results, indicating the need for future research. This study examined the factors influencing motorists' compliance with a legislated bicycle passing distance rule in Queensland, Australia. Unlike the earlier studies, which used volunteer riders to record passing events, this study used a naturalistic study design to record passing events where none of the motorists or the cyclists were aware of being studied. As a result, this study captured the 'true' driving and riding behaviours during passing events. The likelihood of non-compliance was greater on higher (70–80 km/h speed limits) and lower (40 km/h) speed roads than 60 km/h roads, at curved road sections, and on roads with narrower traffic lanes. Rider characteristics (age, gender, helmet status, type of clothing, type of bicycle, and individual or group riding) had no statistically significant association with compliance status. The findings indicate that efforts to improve cyclist safety during overtaking events should focus on non-rider related factors, such as roadway infrastructure characteristics.